2019
DOI: 10.2147/jpr.s216807
|View full text |Cite
|
Sign up to set email alerts
|

<p>Nonpharmacological Interventions Addressing Pain, Sleep, and Quality of Life in Children and Adolescents with Primary Headache: A Systematic Review</p>

Abstract: Purpose: Children and adolescents with primary headache are at risk of persistent somatic symptoms and reduced quality of life (Qol) due to pain and pain-related behaviors, such as avoiding school and activities. Sleep is essential to health, and children and adolescents with primary headaches have more sleep complaints than do healthy controls. A treatment approach that addresses multifactorial causes is likely important. Nonpharmacological interventions seem promising. However, knowledge about effective stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 86 publications
(222 reference statements)
0
8
0
Order By: Relevance
“…This study reflects a lower duration of sleep during weekdays and a lower level of general physical activity in the adult group. Sleep hygiene (i.e., regular sleeping patterns and adequate duration of sleep [in general >8 h per night]) and general physical activity strongly correlate with the burden of headache disorders and are an integral part of any migraine education program ( Fernandez-de-Las-Penas et al, 2010 ; Fernandez-de-Las-Penas et al, 2018 ; Klausen et al, 2019 ; Molarius et al, 2008 ; Pavkovic and Kothare, 2020 ; Robberstad et al, 2010 ; Rosenberg et al, 2018 ; Roy et al, 2019 ; Solotareff et al, 2017 ; Torres-Ferrus et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study reflects a lower duration of sleep during weekdays and a lower level of general physical activity in the adult group. Sleep hygiene (i.e., regular sleeping patterns and adequate duration of sleep [in general >8 h per night]) and general physical activity strongly correlate with the burden of headache disorders and are an integral part of any migraine education program ( Fernandez-de-Las-Penas et al, 2010 ; Fernandez-de-Las-Penas et al, 2018 ; Klausen et al, 2019 ; Molarius et al, 2008 ; Pavkovic and Kothare, 2020 ; Robberstad et al, 2010 ; Rosenberg et al, 2018 ; Roy et al, 2019 ; Solotareff et al, 2017 ; Torres-Ferrus et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mutual outpatient hours held by child neurologists together with neurologists for patients in their late teen and early twen years could ease transition to adult neurology. Appealingly designed educational material and distribution of information via different kinds of media may represent further key features ( Albers et al, 2015a ; Klausen et al, 2019 ; Kroon Van Diest et al, 2016 ). With regard to lifestyle management, the significance of a well-balanced diet, sleep habits, and physical activity should be addressed.…”
Section: Implications For Practicementioning
confidence: 99%
“…A recent systematic review by Klausen et al, [ 54 ] found that sleep was reported as a treatment outcome in only two published RCTs of CBT-Pain in pediatric samples [ 55 , 56 ]. Sleep assessments included a self-report measure of sleep quality [ 56 ] and seven days of actigraphy monitoring [ 55 ].…”
Section: Interventions To Improve Sleep Health In Pediatric Pain Popu...mentioning
confidence: 99%
“…According to a German study, clinical symptom complaints are common among school-aged children [ 4 ]. Another study indicated that symptoms such as medically unexplained abdominal pain and headache contributed to more than half of school absences [ 5 ], highly impacting academic performance [ 6 ]. It is unclear how these medically unexplained symptoms occurred, but diet advice may affect medically unsolved symptoms in childhood [ 7 ], indicating that these symptoms could be related to food.…”
Section: Introductionmentioning
confidence: 99%